Teoritisasi Komunikasi Dalam Tradisi Sosiokultural - Eko Nugroho (Communicology: Jurnal Ilmu Komunikasi, 2019)
ABSTRACT The Last Samurai is a Hollywood production film made by Edward Zwick (2003) which won 4 (four) Oscars for several categories at the 2004 Academy Award. In this film, we can see Katsumoto and Algreen at first debating or disagreeing about ways the customs. Socioculturally, there are keywords that can be seen in the film's story, namely "culture" and "interaction". First, that there are different cultural settings from the two figures. They think in terms of two different structural meanings. Sociocultural theories provide explanations in many communication contexts. In general, this tradition explains the following ideas (Littlejhon and Foss, 2005: 45). First, our way of understanding, meaning, norms, roles and rules work interactively in communication. Sociocultural traditions authorize communication in a concept of "reproduction of social order". In this case the interaction as a discussion of communication events becomes an activity that involves the symbols that are based on the meaning, interpretation. And in interaction there is also a convention, an agreement based on the division of meaning of symbols between community members that determines the internal factors (self-concept, or identity, etc.) of each group member, so that the order or rules change as the actuality of the communication itself . Keywords: Sociocultural; Social Order; The Last Samurai